(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The article considers the organizational aspects of reengineering the accounting process as an effective method of improving the accounting and analytical support for the management of eco-innovations at domestic enterprises. It is proved that reengineering the process of accounting for eco-innovations allows to provide a clear understanding of the status of eco-innovation projects, reduce the time and resources required for managing eco-innovations and increase the innovative potential of the enterprise. The study developed an adaptive model for reengineering the processes of accounting for eco-innovations, which is a prerequisite for the formation of a single integrated accounting system based on the principles of economic and environmental safety. The model is based on an architecture-oriented approach to the distribution and regulation of information flows, providing effective access to data for managers of all levels to quickly make informed management decisions aimed at achieving sustainable development goals. It is recommended to reengineer the process of accounting for eco-innovations in the management information system of an enterprise by phasing in a new process, which includes: initiation, identification, diagnosis, planning, implementation, monitoring and evaluation. The proposed approach allows timely identification of problems in accounting processes, optimization of accounting processes to ensure effective monitoring of environmental indicators, generation of reports and exchange of data on environmental indicators with stakeholders. The carried out SWOT-analysis of the organization of eco-innovation accounting allowed to identify the strengths and weaknesses of the existing process of eco-innovation accounting, to assess the opportunities and threats faced by the enterprise in the field of eco-innovation implementation, to identify the key factors influencing the eco-innovation activities of the enterprise, to formulate recommendations for improving the accounting of eco-innovations. As new processes for accounting for eco-innovations, the author recommends their digital transformation using such modern solutions as artificial intelligence, machine learning, data analytics, the Internet of Things, and cloud computing. The implementation of the proposed organizational and methodological approaches to reengineering accounting processes will help to optimize the management of eco-innovation activities of domestic enterprises, increasing the transparency and analytical nature of eco-innovation accounting processes.